2022
DOI: 10.1007/s11896-022-09532-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Traumatic Material on Professionals in Analytical and Secondary Investigative Roles Working in Criminal Justice Settings: a Qualitative Approach

Abstract: Professionals in analytical and secondary investigative roles are exposed to violent material on a daily basis with full immersion in the details of serious offenses. However, there is limited evidence of the impact of this on their mental health. Therefore, this research aims to explore the impact of traumatic material on the mental health of these professionals in police and law enforcement and the strategies they employ to cope with the nature of their work. Forty semi-structured interviews were conducted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(38 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Although increased levels of empathy can make an OM more vulnerable to developing compassion fatigue and secondary trauma (Duran and Woodhams, 2022), many of the essential OM skills identified by the MoJ and Probation Service require a high level of empathetic awareness and attunement. Empathy is the ability to determine what someone else is thinking or feeling and to respond appropriately (Baron-Cohen, 2011).…”
Section: Cognitive Emotional and Motor Empathymentioning
confidence: 99%
See 1 more Smart Citation
“…Although increased levels of empathy can make an OM more vulnerable to developing compassion fatigue and secondary trauma (Duran and Woodhams, 2022), many of the essential OM skills identified by the MoJ and Probation Service require a high level of empathetic awareness and attunement. Empathy is the ability to determine what someone else is thinking or feeling and to respond appropriately (Baron-Cohen, 2011).…”
Section: Cognitive Emotional and Motor Empathymentioning
confidence: 99%
“…Evidence shows that police officers and other professionals experience heightened clinical symptoms, including anxiety, depression, simple and complex trauma, as well as increased levels of suicidal ideation and alcohol abuse (Foley et al, 2021;Syed et al, 2020). Working with offenders exposes OMs to daily traumatising information and situations, leading to burnout, compassion fatigue and secondary traumatic stress (Duran and Woodhams, 2022;Hurrell et al, 2017). Organisational factors can increase the experience of mental health problems (Sutton et al, 2022) and have a legal duty of care and ethical responsibility to create and maintain working environments that protect workers from harm (Management of Health & Safety, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous interview study (Duran & Woodhams, 2022 ) with 40 international analytical practitioners, their responses also imply that the medium of exposure, mental imagery, thought suppression and belief in just world could be potential risk factors for psychological distress. Therefore, based on our theoretical arguments and qualitative research findings, we aimed to advance our knowledge of how specified individual and work-related characteristics could act as risk factors for depressive symptoms in these roles.…”
mentioning
confidence: 97%
“…depression and PTSD) (Beck, 1976 ; Beevers et al, 1999 ; Duran & Woodhams, 2023 ). Duran and Woodhams ( 2022 ) found that analytical practitioners cope with the nature of their work by actively suppressing unwanted intrusive thoughts related to traumatic material when they come to mind. However, in the literature (Ehlers & Clark, 2000 ), this is considered maladaptive because the suppression of recollections of the traumatic event can increase the likelihood of them coming back to mind (Miller et al, 2019 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation